Community Organizing and Counter Narratives in the Response to Domestic Violence in India. Issue 1 (26th May 2020) - Menon, Suvarna V.; Allen, Nicole E.
Abstract : Abstract: Domestic violence affects women globally. Domestic violence in India is embedded in structures of patriarchy, cultural norms, and a conservative social structure (Biswas, 2017). Community narratives help to create meaning and impact human behavior and can be tools of empowerment (Rappaport, 1995). They can also provide an important means of detecting changes in norms. Community engagement efforts that focus on empowering communities can play an important role in creating empowering narratives. Organizational settings like grassroots agencies can play a salient role in providing opportunities for community engagement leading to the creation of new community narratives and personal stories. This study sought to examine the work of a grassroots agency in India engaged in community action aimed at social change in the response to domestic violence, with a special focus on understanding shifting community narratives related to the response to domestic violence. Based on data from semi‐structured interviews, archival data, and participant‐observations, and using a modified‐grounded theory approach, our results identified five major themes reflecting counter narratives on domestic violence. These included (a) awareness and discourse on gender related issues, (b) framing domestic violence as a social issue, (c) supporting the empowerment of women, (d) supporting disclosure of violence, and (e) supporting intervening in cases of violence. Implications of our findings for social change work in the response to domestic violence are discussed. Highlights: Community narratives can provide an important means of detecting changes in norms. Social movements can target and change community narratives to redefine problems. Community engagement that empowers communities can create empowering narratives. This study highlights various counter narratives in the response to domestic violence. Implications for social change work are discussed.